107 Imaging features of preoperative wilms tumour rupture on CT and MRI with histopathological confirmation. (December 2018) - Adu, J; Watson, T
Abstract : Background: Preoperative Wilms tumour rupture is an uncommon, but potentially significant phenomenon owing to its adverse effect on prognosis because of tumour dissemination. The International Society of Paediatric Oncology (SIOP) recommends that ruptured tumours are upstaged to IIIc, necessitating intensive chemotherapy and whole abdomen radiotherapy. As yet, there are no radiological features to diagnose Wilms tumour rupture unequivocally. However, there are some imaging findings that may indicate that rupture has occurred. The aim of this study is to illustrate the radiological features suggestive of Wilms tumour rupture. Aims: We retrospectively searched the histopathology database at our tertiary referral centre over a 10 year period using the search terms 'Wilms resection' to identify patients. Cases of histologically proven ruptured were then cross-checked with their associated imaging on our PACS, and selected for presentation. Results: 187 patients with Wilms tumour were identified. Of these, 4 had ruptured. Common imaging features were the presence of ascites, irregularity of tumour margin and perinephric fat stranding. Conclusion: Radiological detection of preoperative Wilms tumour rupture is challenging. Radiologists must be alert to the imaging features which may indicate tumour rupture in order to guide appropriate subsequent management.